Evolution of ASEAN financial integration in the comparative perspective - Danupon Ariyasajjakorn; Pitchaya Sirivunnabood; Matteo Molineris (Asian Development Bank Institute (ADBI), 2020)
Since the Asian financial crisis of 1997-1998, the Association of Southeast Asian Nations (ASEAN) has continuously worked on the context of financial integration and put tremendous effort into ensuring financial stability in the region. Two ASEAN Economic Community (AEC) blueprints have been endorsed with elements of financial integration and liberalization, toward its goal of achieving regional financial integration and the complement of financial inclusion and financial stability. Though the effort seems ambitious, regional initiatives have been agreed and partly implemented in the areas of banking, insurance, capital accounts, capital markets, payment and settlement systems, taxation, financial inclusion, financial stability, financial resilience, and sustainable finance. Given the long-standing process of financial integration of the European Union (EU), and the proven tangible economic benefits associated with a significant degree of financial integration, ASEAN could learn from the EU's experience, particularly under the current global challenges. This paper reviews ASEAN's process, which includes financial integration and financial stability, in comparison with that of the EU. The paper examines the effectiveness of the initiatives agreed and implemented by ASEAN against the EU's success story as an institutional benchmark. A set of conclusions and policy recommendations are derived at the end of this paper.
Keywords: F36; 330; financial integration; EU; ASEAN; economic integration; ASEAN Economic Community; financial stability